2021
DOI: 10.1002/slct.202004755
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antimicrobial Activity, Anti‐HIV Activity, and Molecular Docking of Novel 5‐, 6‐ and 7‐Membered Ring (1H‐Pyrrol‐2‐yl)aminolactams

Abstract: An efficient method has been developed for the synthesis of novel 5‐, 6‐ and 7‐membered ring (1H‐pyrrol‐2‐yl)aminolactams 5 a–f. This method featured Ugi‐4‐center‐3‐component reaction (U4 C3 C) followed by a post‐transformation reaction. All the newly synthesized (1H‐pyrrol‐2‐yl)aminolactams 5 a–f have been screened against six microbial species and the results revealed that these lactams exhibited moderate to good activity. These lactams were also tested in an in vitro for their antiviral activity against of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…Recently, cyclic amides, known as lactams, coupled with pyrrole have proven to be a promising group in the search for an anti-HIV drug candidate, as demonstrated by compound 38 (Figure 16) [83]. Within a set of six compounds, 38 was the only compound active at a noncytotoxic concentration, showing an EC 50 of 2.74 ± 1.08 µM (CC 50 18.93 ± 4.0 µM) against HIV-1; however, 38 was inactive against replication in the HIV-2 cell line (Table 3).…”
Section: Pyrrole-based Anti-hiv-1 Inhibitors (Dual Inhibitors Rt Inhibitors and Replication Inhibitors)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, cyclic amides, known as lactams, coupled with pyrrole have proven to be a promising group in the search for an anti-HIV drug candidate, as demonstrated by compound 38 (Figure 16) [83]. Within a set of six compounds, 38 was the only compound active at a noncytotoxic concentration, showing an EC 50 of 2.74 ± 1.08 µM (CC 50 18.93 ± 4.0 µM) against HIV-1; however, 38 was inactive against replication in the HIV-2 cell line (Table 3).…”
Section: Pyrrole-based Anti-hiv-1 Inhibitors (Dual Inhibitors Rt Inhibitors and Replication Inhibitors)mentioning
confidence: 99%
“…Within a set of six compounds, 38 was the only compound active at a noncytotoxic concentration, showing an EC 50 of 2.74 ± 1.08 µM (CC 50 18.93 ± 4.0 µM) against HIV-1; however, 38 was inactive against replication in the HIV-2 cell line (Table 3). The docking analysis carried out with crystal structures of RT of HIV-1 and HIV-2 suggested that compound 38 was a potent HIV-1 NNRTI agent [83]. In an attempt to obtain active compounds in cells infected by HIV-1, Yonn et al [82] synthesized new scaffolds of pyrrolo-pyridine derivatives (Figure 16).…”
Section: Pyrrole-based Anti-hiv-1 Inhibitors (Dual Inhibitors Rt Inhibitors and Replication Inhibitors)mentioning
confidence: 99%
“…1.3 分子对接 分子对接已被证明是研究蛋白质和小分子配体相 互作用的有效工具 [17] . 根据化合物 8a~8r 的细胞活性 和 EGFR 抑制活性结果, 化合物 8a、 8l 对 HepG2、 A549、 Hela、MCF-7、A549/DDP 细胞均具有良好的抑制活性, 且它们对 EGFR 在 0.01 μmol/L 浓度下的抑制作用较弱, 在高浓度下对 EGFR 又具有良好的抑制作用.…”
unclassified